2016
DOI: 10.1002/2015jb012778
|View full text |Cite
|
Sign up to set email alerts
|

New insights into Phanerozoic tectonics of south China: Part 1, polyphase deformation in the Jiuling and Lianyunshan domains of the central Jiangnan Orogen

Abstract: The central Jiangnan Orogen, genetically formed by the Proterozoic Yangtze‐Cathaysia collision, presents as a composite structural feature in the Phanerozoic with multiple ductile and brittle fabrics whose geometries, kinematics, and ages are crucial to decipher the tectonic evolution of south China. New structural observations coupled with thermochronological and geochronological studies of these fabrics document four main stages of deformation. The earliest stage in early Paleozoic time (460–420 Ma) correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 124 publications
(314 reference statements)
7
99
0
Order By: Relevance
“…440 Ma, during the Caledonian period. An increasing number of studies have demonstrated that the Caledonian Orogen in the SCB (>460–415 Ma), also known as the Wuyi–Yunkai Orogen, was an intraplate orogenic event (e.g., Charvet et al, ; Faure et al, ; Z. X. Li et al, ; J. H. Li et al, ; Shu et al, ; Y. J. Wang, Zhang, et al, ; Yao et al, ) rather than a continental or arc collisional event involving the closure of the proposed Huanan Ocean within the SCB (Guo et al, ; Hsü, ; Hsü et al, ). Models of crustal anatexis (L. Wang et al, ) and lithospheric delamination or orogenic collapse (Z. X. Li et al, ; Shu et al, ; Y. J. Wang, Zhang, et al, ; Yao et al, ; Yu et al, ) have been put forward to explain the Caledonian structural elements, metamorphism, and magmatism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…440 Ma, during the Caledonian period. An increasing number of studies have demonstrated that the Caledonian Orogen in the SCB (>460–415 Ma), also known as the Wuyi–Yunkai Orogen, was an intraplate orogenic event (e.g., Charvet et al, ; Faure et al, ; Z. X. Li et al, ; J. H. Li et al, ; Shu et al, ; Y. J. Wang, Zhang, et al, ; Yao et al, ) rather than a continental or arc collisional event involving the closure of the proposed Huanan Ocean within the SCB (Guo et al, ; Hsü, ; Hsü et al, ). Models of crustal anatexis (L. Wang et al, ) and lithospheric delamination or orogenic collapse (Z. X. Li et al, ; Shu et al, ; Y. J. Wang, Zhang, et al, ; Yao et al, ; Yu et al, ) have been put forward to explain the Caledonian structural elements, metamorphism, and magmatism.…”
Section: Discussionmentioning
confidence: 99%
“…210 Ma) in the Dabaoshan ore district, together with coeval mafic–ultramafic magmatic rocks (e.g., Dai, Jiang, Jiang, Zhao, & Liu, ; Liang, Fan, Wang, & Li, ), indicate that lithospheric extension took place in the SCB during the late Indosinian. A number of competing models have been invoked to explain the extension, such as the flat subduction of the Palaeo‐Pacific Plate (Z. X. Li & Li, ), but the current consensus is that the Indosinian Orogeny (248–200 Ma) in the SCB was an intraplate orogenic event (e.g., J. H. Li et al, ; Shu et al, ; Y. J. Wang et al, ; Y. J. Wang, Fan, et al, , and reference therein) similar to the Caledonian Orogeny. The late Indosinian granites, mafic–ultramafic rocks, and volcanics in the SCB were generated by the partial melting of the lower crust and subcontinental lithospheric mantle due to lithospheric delamination or orogenic collapse, and the upwelling of asthenosphere and underplating of basalts (220–200 Ma).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biotite Ar/Ar dating gave Neoproterozoic ages (Hu et al, ), and zircon U‐Pb dating yield concordant ages of circa 800–830 Ma for the Jiuling batholith (Li et al, ; Wang et al, ; Zhong et al, ; Zhao et al, ). Although most of the batholith show no evidence of metamorphic overprint, multiple faults with deformation ages ranging from the Paleozoic to Mesozoic were developed in the Jiuling batholith and its adjacent area (Chu & Lin, ; Li et al, ). The Jiuling batholith is intruded by a small Mesozoic granitic pluton with ages of about 150 Ma (Zhong et al, ).…”
Section: Geological Setting and Samplesmentioning
confidence: 99%